Pilomatricoma of the auricular region: case report - Silva,Tarcília Aparecida da (2003)
Pilomatricomas are relatively rare tumors of ectodermal origin from the outer root sheath cell of the hair follicle. They are usually asymptomatic, solitary, firm or hard, freely mobile, dermal or subcutaneous nodules. The purpose of this article is to present a case that illustrates the diagnostic difficulty encountered by oral surgeons and pathologists and to review the literature regarding pilomatricomas of the auricular region.